2017
DOI: 10.1515/pjct-2017-0076
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of iron oxide nanoparticles synthesized by co-precipitation technology against Bacillus cereus and Klebsiella pneumoniae

Abstract: The present study investigates the synthesis and characterization of iron oxide nanoparticles (Fe 3 O 4 -NPs) for their antibacterial potential against Bacillus cereus and Klebsiella pneumonia by modifi ed disc diffusion and broth agar dilution methods. DLS and XRD results revealed the average size of synthesized Fe 3 O 4 -NPs as 24 nm while XPS measurement exhibited the spin-orbit peak of Fe 2p 3/2 binding energy at 511 eV. Fe 3 O 4 -NPs inhibited the growth of K. pneumoniae and B. cereus in both liquid and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 28 publications
1
19
0
2
Order By: Relevance
“…As the antimicrobial activity of IONPs and their derivatives is a matter of intensive debate ( Auffan et al, 2008 ; Chatterjee et al, 2011 ; Borcherding et al, 2014 ; Arakha et al, 2015a ; Ansari et al, 2017 ), we further investigated the effects of IONPs, NP-APTES, and NP-TEICO on bacterial cell viability, by adding our NP preparations at the log phase of the growth kinetics of S. aureus ATCC 6538P, B. subtilis ATCC 6633, and E. coli ATCC 35218 populations. Cultures with no added NP or to which only teicoplanin was added were used as negative and positive controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the antimicrobial activity of IONPs and their derivatives is a matter of intensive debate ( Auffan et al, 2008 ; Chatterjee et al, 2011 ; Borcherding et al, 2014 ; Arakha et al, 2015a ; Ansari et al, 2017 ), we further investigated the effects of IONPs, NP-APTES, and NP-TEICO on bacterial cell viability, by adding our NP preparations at the log phase of the growth kinetics of S. aureus ATCC 6538P, B. subtilis ATCC 6633, and E. coli ATCC 35218 populations. Cultures with no added NP or to which only teicoplanin was added were used as negative and positive controls.…”
Section: Resultsmentioning
confidence: 99%
“…Although IONPs and NP-APTES have shown some antibacterial effect against diverse Gram-positive and Gram-negative bacteria, the real extent of this phenomenon and the underlying mechanism has hitherto not been well understood ( Baranwal et al, 2018 ). Ansari et al (2017) reported a dose-dependent antibacterial activity of IONPs against Bacillus cereus and Klebsiella pneumoniae. In contrast, Auffan et al (2008) indicated that chemically stable IONPs were not toxic to E. coli at 700 mg/L, whereas Chatterjee et al (2011) reported a dose-dependent effect on E. coli cells.…”
Section: Discussionmentioning
confidence: 99%
“…Both ionic iron and iron nanoparticles are being proposed as methods for controlling multi-drug resistant bacteria, [ 21–23 ] as they have even been shown to enhance the activity of traditional antibiotics [ 24–26 ]. For example, against Escherichia coli, Fe 2+ -loaded chitosan nanoparticles have an minimum inhibitory concentration (MIC) of 10 mg/ml with even better activity against gram-positive bacteria and have been furthermore proposed to be used as a food preservative [ 27 ].…”
Section: Background and Objectivementioning
confidence: 99%
“…The antimicrobial activity of Fe 2 O 3 NPs could be due to their accumulation in the cytoplasm because smaller NPs have a greater capacity to penetrate the cell membrane. This would cause leakage of cellular material as well as NP accumulation inside the cell, increasing the interaction between the Fe 2 O 3 NPs and the cellular biomolecules, causing conformational changes in the structure of the proteins and the DNA, which finally leads to the death of the bacteria 173,174 …”
Section: Nanoparticles With Antimicrobial Activity Against Phytopathomentioning
confidence: 99%
“…This would cause leakage of cellular material as well as NP accumulation inside the cell, increasing the interaction between the Fe 2 O 3 NPs and the cellular biomolecules, causing conformational changes in the structure of the proteins and the DNA, which finally leads to the death of the bacteria. 173,174 Another possible antimicrobial mechanism of action of Fe 2 O 3 NPs is the production of ROS ( 1 O 2 , HO 2…”
Section: Iron Oxide Nanoparticles (Fe 2 O 3 Nps)mentioning
confidence: 99%